2003
DOI: 10.1038/sj.cdd.4401228
|View full text |Cite
|
Sign up to set email alerts
|

Antiandrogen-induced cell death in LNCaP human prostate cancer cells

Abstract: Antiandrogens such as Casodex (Bicalutamide) are designed to treat advance stage prostate cancer by interfering with androgen receptor-mediated cell survival and by initiating cell death. Treatment of androgen sensitive, non-metastatic LNCaP human prostate cancer cells with 0-100 microM Casodex or 0-10 ng/ml TNF-alpha induces cell death in 20-60% of the cells by 48 h in a dose-dependent manner. In cells treated with TNF-alpha, this is accompanied by the loss of mitochondrial membrane potential (DeltaPsim) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
38
0
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 42 publications
(43 reference statements)
6
38
0
2
Order By: Relevance
“…5 There is emerging evidence to show that bicalutamide exerts its proapoptotic effects independent of mitochondrial membrane changes and that a by-product of caspase 8 is produced as a result of caspase 3 action. 13 Paradoxically, there is evidence to suggest that bicalutamide in advanced disease may be agonistic in nature. Some authors have reported that bicalutamide works as an agonist in cells derived from prolonged periods of androgen ablation, leading to an androgenindependent (LNCaP-abl) cell line.…”
Section: Discussionmentioning
confidence: 99%
“…5 There is emerging evidence to show that bicalutamide exerts its proapoptotic effects independent of mitochondrial membrane changes and that a by-product of caspase 8 is produced as a result of caspase 3 action. 13 Paradoxically, there is evidence to suggest that bicalutamide in advanced disease may be agonistic in nature. Some authors have reported that bicalutamide works as an agonist in cells derived from prolonged periods of androgen ablation, leading to an androgenindependent (LNCaP-abl) cell line.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] It is well demonstrated that castration in rodent models or androgen ablation in cell culture system causes a rapid apoptotic response in the prostate-derived epithelial cells. 4,5 Based on these phenomena, androgen ablation therapy has been used in clinical management of prostate cancer patients. 6 However, the disease progresses to a more aggressive androgen-independent stage (termed 'hormonerefractory' because the tumor is resistant to androgen ablation therapy).…”
mentioning
confidence: 99%
“…By targeting AR, WT-ANXA7 represented a potential alternative to antiandrogens which may promote tumor invasiveness. 45 Because of the gain of function, AR becomes an oncogene in type-II androgen depletion insensitive cells, but not in the type-I DU145 and PC3. In fact, RB1 can activate AR-dependent apoptosis, 8,21 and the reinforced AR can still function as a tumor suppressor in PC3 cells.…”
Section: Discussionmentioning
confidence: 99%